The Intersection of Faith and Mental Health: Promoting Holistic Well-Being in Evangelical Christian Communities (Impact: Journal of Transformation, 2024)
This study is a quantitative research investigation into the dynamic relationship between faithand mental health in the youth within an evangelical urban Christian community in Nairobi,Kenya. Through an in-depth analysis of existing literature, and data collected from structuredinterviews, this research sought to shed light on the ways in which faith principles and mentalhealth practices intersect. This research explored how different theological frameworks andcommunity structures influence attitudes towards mental health and the provision of supportneeded. The participants were selected through purposive sampling of individuals from theYouth Ministry of Mamlaka Hill Chapel, which is an evangelical urban Christian communitylocated within the campus hostel grounds of the University of Nairobi, Kenya. The samplesize involved 54 students drawn from a population of 400 youths who frequent the church.Key findings highlighted the importance of destigmatizing mental illnesses through educationprograms, and the availability of resources for individuals facing mental health challengeswithin Christian congregations. While this study was limited to structured interviews, thefindings highlighted best practices and recommendations for promoting mental healthawareness and support within faith-based settings whilst providing insight into the potentialstrategies for reduced stigma surrounding mental illness. By acknowledging theinterconnectedness of faith and mental health, the need for collaboration between mentalhealth professionals, clergy, and congregants is needed to provide comprehensive care thataddresses both the spiritual and psychological aspects of well-being. In conclusion, the1 Impact: Journal of Transformation Vol. 7 (2) 2024, ISSN 2617-5576findings from this study underscore the need for targeted interventions to address mentalhealth stigma within Christian communities and enhance support structures for individualsnavigating mental health challenges. This research contributes to the ongoing dialogue onholistic well-being and the prioritizing of mental health awareness and support, and theintegration of faith principles in mental health support systems